2019
DOI: 10.3390/md17110598
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fromiamycalin and Halaminol A from Australian Marine Sponge Extracts with Anthelmintic Activity against Haemonchus contortus

Abstract: There is an urgent need to discover and develop new anthelmintics for the treatment of parasitic nematodes of veterinary importance to circumvent challenges linked to drug resistant parasites. Being one of the most diverse natural ecosystems, the marine environment represents a rich resource of novel chemical entities. This study investigated 2000 extracts from marine invertebrates, collected from Australian waters, for anthelmintic activity. Using a well-established in vitro bioassay, these extracts were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…(CMB-03107) [ 86 ]. Finally, a moderate to limited inhibition of H. contortus motility was recently documented for fromiamycalin, a pentacyclic guanidine alkaloid, and halaminol A, an acetamide that were isolated from the extracts of the demosponges Monanchora unguilata and Haliclona sp., respectively [ 87 ].…”
Section: Spongesmentioning
confidence: 99%
“…(CMB-03107) [ 86 ]. Finally, a moderate to limited inhibition of H. contortus motility was recently documented for fromiamycalin, a pentacyclic guanidine alkaloid, and halaminol A, an acetamide that were isolated from the extracts of the demosponges Monanchora unguilata and Haliclona sp., respectively [ 87 ].…”
Section: Spongesmentioning
confidence: 99%
“…Although there has been a major focus on synthetic compounds as anthelmintics [8,14], recent studies have shown that natural compounds from both terrestrial and marine environments have shown considerable promise [15][16][17][18][19] due to the diverse biologically active chemotypes in nature [20]. Current estimates indicate that there are >400,000 land plant species and ≥44,000 species of algae [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Alcaloides: Con los cuales se dio el inicio formal al estudio de los MSP cuando el farmacéutico alemán Friedrich Sertürner aisló la morfina en el año 1806 (32). Esta familia de MSP posee unas 20,000 estructuras identificadas (39) y sus propiedades AH son materia actual de estudio (40,41).…”
Section: Metabolitos Secundarios De Las Plantas Y Sus Propiedades Antihelmínticasunclassified